2015
DOI: 10.1016/j.bpj.2015.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Transbilayer Colocalization of Lipid Domains Explained via Measurement of Strong Coupling Parameters

Abstract: When micron-scale compositional heterogeneity develops in membranes, the distribution of lipids on one face of the membrane strongly affects the distribution on the other. Specifically, when lipid membranes phase separate into coexisting liquid phases, domains in each monolayer leaflet of the membrane are colocalized with domains in the opposite leaflet. Colocalized domains have never been observed to spontaneously move out of registry. This result indicates that the lipid compositions in one leaflet are stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 77 publications
(116 reference statements)
5
73
3
Order By: Relevance
“…Such movement is only observed upon exposure to large hydrodynamic forces. However, ordered domains in the nonadhering leaflet that are forced out of register with domains in the adhering monolayer do not move back into register when no longer exposed to the hydrodynamic force (8). Thus, it is no surprise that atomic force experiments on supported bilayers reported the misalignment of domains in the individual leaflets (34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such movement is only observed upon exposure to large hydrodynamic forces. However, ordered domains in the nonadhering leaflet that are forced out of register with domains in the adhering monolayer do not move back into register when no longer exposed to the hydrodynamic force (8). Thus, it is no surprise that atomic force experiments on supported bilayers reported the misalignment of domains in the individual leaflets (34).…”
Section: Resultsmentioning
confidence: 99%
“…It has never been observed that two such L o domains spontaneously decouple. On the contrary, it took considerable hydrodynamic shear stress to move domains in one leaflet of a supported bilayer out of register with domains in the other leaflet (8).…”
Section: Introductionmentioning
confidence: 99%
“…To explain this observed registration between domains, several physical mechanisms have been proposed, such as cholesterol flip-flop and dynamic chain interdigitation (11) and complex interplay between chain entropic and energetic effects (12). As for the strength of the interleaflet coupling, L, theoretical predictions range from $ 1 k B T=nm 2 (11,13) to $ 0:01 k B T=nm 2 (12), while very recent experimental work employing a microfluidics approach in conjunction with a supported bilayer system has obtained a value of Lz0:016 k B T= nm 2 for a representative ternary lipid system (14). To put these values in perspective, as shown in (12), the characteristic width of the mismatched region resulting from out-of-alignment fluctuations is given by x t ¼ ½ðk B TÞ 2 =ðLtÞ 1=3 , where t $ 10 À12 N denotes the line tension between Ld/Lo domains away from a critical point (2).…”
Section: Introductionmentioning
confidence: 99%
“…1D [1,42]. (Recent estimates of this difference are an order of magnitude lower [34,35], implying a concomitantly greater sensitivity to a given strength of external field.) Fig.…”
Section: Effect Of An External Fieldmentioning
confidence: 99%
“…As discussed in [34], the relation between the geometry of thickness mismatch in supported bilayers and that in free-floating ones is not understood and is a matter of active research. Ref.…”
Section: Experiments That Probe Phase Diagram Topologymentioning
confidence: 99%